Ewolucyjny obraz przekształceń systemu ochrony zdrowia w Polsce - Ćwiąkała-Małys, Anna; Łagowski, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
In the article the evolution of the health care system in Poland over the last century is presented. The article contains a description of works and the shape of particular reform stages up to today. The essence of the reform of the inefficient budget system is emphasised. Moreover, in the article it is shown that different political options have made developing of the proper health care system in Poland unsuccessful.
Keywords: health care system; Poland; transformation of health care